2012
DOI: 10.1039/c1cp22358e
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast vibrational energy relaxation of the water bridge

Abstract: We report the energy relaxation of the OH stretch vibration of HDO molecules contained in an HDO:D(2)O water bridge using femtosecond mid-infrared pump-probe spectroscopy. We found that the vibrational lifetime is shorter (~630 ± 50 fs) than for HDO molecules in bulk HDO:D(2)O (~740 ± 40 fs). In contrast, the thermalization dynamics following the vibrational relaxation are much slower (~1.5 ± 0.4 ps) than in bulk HDO:D(2)O (~250 ± 90 fs). These differences in energy relaxation dynamics strongly indicate that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 18 publications
3
27
0
Order By: Relevance
“…In a HDO:D 2 O water bridge, for instance, the lifetime of the local OH stretch vibration of HDO molecules was found to be shorter than in the bulk, while its delocalization by thermalized relaxation lasted longer. 259 The core of the bridge contains water with H þ ions and ice-like features, while the outer shell contains more OHions. 260 In the bridge, a higher H þ mobility than in bulk water has been measured, explained with a stronger hydrogen bond and therefore stronger intermolecular proton delocalization.…”
Section: E Liquids In Strong Fields: Can the Floating Water Bridge Hmentioning
confidence: 99%
“…In a HDO:D 2 O water bridge, for instance, the lifetime of the local OH stretch vibration of HDO molecules was found to be shorter than in the bulk, while its delocalization by thermalized relaxation lasted longer. 259 The core of the bridge contains water with H þ ions and ice-like features, while the outer shell contains more OHions. 260 In the bridge, a higher H þ mobility than in bulk water has been measured, explained with a stronger hydrogen bond and therefore stronger intermolecular proton delocalization.…”
Section: E Liquids In Strong Fields: Can the Floating Water Bridge Hmentioning
confidence: 99%
“…Accordingly, such ion-molecule interactions have been extensively studied by FTIR experiments and theoretical methods for a few decades [1][2][3][4][5][6][7]. However, the effect of ions on vibrational dynamics of a given molecule has begun to be investigated recently with an advent of time-resolved vibrational spectroscopic techniques such as ultrafast infrared-Raman, infrared pump-probe (IR PP), and two-dimensional IR (2DIR) experiments [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. A vibrationally excited molecule undergoes different relaxation processes on various timescales including vibrational energy transfer to anharmonically coupled vibrational modes [23,24], vibrational energy dissipation into the solvent [25], and resonance energy transfer to nearby vibrational modes with similar vibrational energies [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The key observations in water bridges that motivated this study were: Density gradients (7% edge to core) observed using optical techniques (6), anisotropy observed in neutron scattering (9), optical birefringence from polarized light scattering (11,12) and changes in the OH stretch vibration from Raman and infrared measurements (10,13).…”
mentioning
confidence: 99%